2022
DOI: 10.1002/adfm.202203001
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Number Dependent Catalytic Activity of Single‐Atom Cobalt Catalysts for Fenton‐Like Reaction

Abstract: Single‐atom catalysts (SACs) are widely investigated in Fenton‐like reactions for environmental remediation, wherein their catalytic performance can be further improved by coordination structure modulation, but the relevant report is rare. Herein, a series of atomically dispersed cobalt catalysts with diverse coordination numbers (denoted as CoNx, x represents nitrogen coordination number) are synthesized and their peroxymonosulfate (PMS) conversion performance is explored. The catalytic specific activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(74 citation statements)
references
References 46 publications
3
54
1
Order By: Relevance
“…The more significant suppression effect for FFA on BPA degradation suggests that 1 O 2 is the primary ROS, which can be also evidenced by the enhancement of BPA oxidation (Figure 4e) and improvement of 1 O 2 formation (Figure 4f) in Fe-CN 0.05 /PMS with the solvent exchange from H 2 O to deuterium oxide (D 2 O), owing to the tenfold extension for the lifetime of 1 O 2 in D 2 O relative to that in H 2 O. [15,47] Small 2023, 19, 2205583 As for Fe-based catalysts applied in organic pollutant degradation, high-valence Fe species have been reported to form and involve in the catalytic oxidation reaction. [48,49] In this regard, methyl phenyl sulfoxide (PMSO) was poured into the air-equilibrated Fe-CN 0.05 /PMS system to evaluate the contribution of high-valent Fe species to BPA degradation.…”
Section: • −mentioning
confidence: 82%
See 2 more Smart Citations
“…The more significant suppression effect for FFA on BPA degradation suggests that 1 O 2 is the primary ROS, which can be also evidenced by the enhancement of BPA oxidation (Figure 4e) and improvement of 1 O 2 formation (Figure 4f) in Fe-CN 0.05 /PMS with the solvent exchange from H 2 O to deuterium oxide (D 2 O), owing to the tenfold extension for the lifetime of 1 O 2 in D 2 O relative to that in H 2 O. [15,47] Small 2023, 19, 2205583 As for Fe-based catalysts applied in organic pollutant degradation, high-valence Fe species have been reported to form and involve in the catalytic oxidation reaction. [48,49] In this regard, methyl phenyl sulfoxide (PMSO) was poured into the air-equilibrated Fe-CN 0.05 /PMS system to evaluate the contribution of high-valent Fe species to BPA degradation.…”
Section: • −mentioning
confidence: 82%
“…The more significant suppression effect for FFA on BPA degradation suggests that 1 O 2 is the primary ROS, which can be also evidenced by the enhancement of BPA oxidation (Figure 4e) and improvement of 1 O 2 formation (Figure 4f) in Fe‐CN 0.05 /PMS with the solvent exchange from H 2 O to deuterium oxide (D 2 O), owing to the tenfold extension for the lifetime of 1 O 2 in D 2 O relative to that in H 2 O. [ 15,47 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that in the Co-BOC/PMS system, the SO 3 − (HSO 5 − ) peak splits into two small peaks located at 1,051 cm −1 and 1,062 cm −1 . And the characteristic vibrational peaks of the SO 3 − (HSO 5 − ) appear both red shifted (1,051 cm −1 ) and blue shifted (1,062 cm −1 ), suggesting that electron transfer occurs between the asymmetric sites and the PMS as well as the orientation may be different ( 47 49 ). Combined with XPS analysis, it can be concluded that the red shift and blue shift come from PMS gaining electrons from the Bi site and losing electrons at the Co site, respectively.…”
Section: Reactive Oxygen Species (Ros) and Their Contribution To Mp D...mentioning
confidence: 99%
“…The coordination number of M–N moieties in SACs strongly affects the geometric and electronic properties, as well as the catalytic activity of SACs. While SACs with a coordination number higher than four have been used for selective conversion of hydrocarbons and oxygen reduction reactions and play prominent roles in biomimetic and enzymatic oxidation reactions, the five-nitrogen coordinated SACs are seldom explored for persulfate activation except for Fe–N 5 SACs. , This represents a fundamental knowledge gap and a missed opportunity for coordination chemistry using other transition metal SACs (such as Co, Mn, Cu, and Ni) to boost PMS activation and enhance the degradation of recalcitrant organic pollutants. For instance, while Mn SACs have been tested for HVMO-dominated persulfate activation, five-nitrogen coordinated Mn SACs have not.…”
Section: Introductionmentioning
confidence: 99%